2020
DOI: 10.36899/japs.2021.3.0255
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Estrus Synchronization Protocols in Non-Descript Cattle of Azad Jammu and Kashmir During Non-Breeding and Breeding Seasons

Abstract: A study was undertaken to investigate the effect of three rearing systems (free range, semi-intensive and confinement) on reproductive performance in four varieties of indigenous Aseel chicken (Lakha, Mushki, Peshawari and Sindhi). A total of 192 adult birds (168 females and 24 males), 48 from each variety, were subjected to 3 rearing systems under Randomized Complete Block Design (RCBD) in a factorial experiment. Data regarding reproductive performance [settable eggs (%), fertility (%), hatch of fertile (%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
5
1
0
Order By: Relevance
“…None of the cows in groups D were pregnant (control). Results are consistent with Shahid et al (2021), who found that the 7-day CIDR procedure had a greater pregnancy rate. When heifers were given the CO-Synch+CIDR treatment, Estrada et al (2002) saw a 60% pregnancy rate.…”
Section: Conception Ratesupporting
confidence: 90%
See 3 more Smart Citations
“…None of the cows in groups D were pregnant (control). Results are consistent with Shahid et al (2021), who found that the 7-day CIDR procedure had a greater pregnancy rate. When heifers were given the CO-Synch+CIDR treatment, Estrada et al (2002) saw a 60% pregnancy rate.…”
Section: Conception Ratesupporting
confidence: 90%
“…Variation in estrus response might be associated with the estrus synchronisation protocol used in different groups. Results are consistent with those of Shahid et al (2021), who found that the estrus response in Sahiwal cows was 87% (40/46), while Hassan et al (2017) found that the estrus response in nondescript indigenous cows was 95.45% when recorded with Ovsynch therapy in the field. The outcomes of the CIDR CO-Synch treatments for estrus response are consistent with those of Haider et al (2017), who found 82.5% and 90% estrus responses in CIDR alone and CIDR combined with GnRH treated nondescript cows of Punjab (Pakistan).…”
Section: Conception Ratesupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, Eski et al (2021) reported higher fertility parameters and antioxidant defense system in hair goats with combined treatment of PGF2α, GnRH, and intravaginal progesterone. An earlier study (Shahid et al, 2021) reported that protocols of Ovsynch in cows, and CO-Synch+CIDR in heifers may result in better CR/TAI and therefore can be used to enhance the genetic improvement through AI and improve the reproductive parameters.…”
Section: Conception/ Pregnancy Ratesmentioning
confidence: 99%